PENGUATAN RESILIENSI PSIKOLOGIS MELALUI REFLEKSI EMOSI POSITIF PADA KONFLIK TEMAN SEBAYA: SYSTEMATIC LITERATURE REVIEW - Nur Afifa; Akhmad Harum; M. Amirullah; Salmiati Salmiati (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT The low level of junior high school students’ psychological resilience, particularly in the dimension of emotional regulation, limits their ability to manage peer conflict constructively, as reported in various national and international studies. Meanwhile, school counseling services remain predominantly reactive and have not systematically facilitated students’ positive emotional reflection skills. This study aimed to synthesize empirical evidence regarding the contribution of positive emotional reflection to strengthening junior high school students’ psychological resilience in dealing with peer conflict. The study employed a systematic literature review method with a narrative synthesis approach by searching articles indexed in Google Scholar and Scopus published between 2015 and 2025 using the keywords psychological resilience, positive emotional reflection, peer conflict, and emotional regulation. A total of 25 national and international articles that met the inclusion criteria were analyzed thematically. The findings revealed that low student resilience is closely associated with weak emotional regulation and limited psychosocial peer support. In addition, positive emotional reflection was found to help students develop emotional regulation, self-adaptation, and psychological resilience in coping with interpersonal conflict. The review also identified a gap between the need for resilience-strengthening interventions and the availability of structured counseling services in schools. These findings imply the importance of developing activity-based positive emotional reflection modules as preventive and systematic interventions to strengthen junior high school students’ psychological resilience. ABSTRAK Rendahnya psychological resilience siswa SMP, terutama pada dimensi regulasi emosi, menghambat kemampuan mereka mengelola konflik sebaya secara konstruktif dalam berbagai studi nasional maupun internasional, sementara layanan bimbingan dan konseling di sekolah masih bersifat reaktif dan belum melatih kemampuan refleksi emosi positif secara terstruktur. Penelitian ini bertujuan mensintesis bukti literatur mengenai kontribusi refleksi emosi positif terhadap penguatan psychological resilience siswa SMP dalam menghadapi konflik sebaya. Metode yang digunakan adalah systematic literature review dengan pendekatan narrative synthesis melalui penelusuran artikel pada Google Scholar dan Scopus tahun 2015–2025 menggunakan kata kunci psychological resilience, refleksi emosi positif, konflik sebaya, dan regulasi emosi. Sebanyak 25 artikel nasional dan internasional yang memenuhi kriteria inklusi dianalisis secara tematik. Hasil kajian menunjukkan bahwa rendahnya resiliensi siswa berkaitan erat dengan lemahnya regulasi emosi dan keterbatasan dukungan psikososial teman sebaya. Selain itu, refleksi emosi positif terbukti membantu siswa mengembangkan kemampuan regulasi emosi, adaptasi diri, dan ketahanan psikologis dalam menghadapi konflik interpersonal. Kajian ini juga menemukan adanya kesenjangan antara kebutuhan intervensi penguatan resiliensi dengan ketersediaan layanan BK yang terstruktur di sekolah. Temuan penelitian mengimplikasikan pentingnya pengembangan modul refleksi emosi positif berbasis aktivitas sebagai intervensi preventif dan sistematis untuk memperkuat psychological resilience siswa SMP.